2003
DOI: 10.2337/diabetes.52.12.2935
|View full text |Cite
|
Sign up to set email alerts
|

Brain Death Significantly Reduces Isolated Pancreatic Islet Yields and Functionality In Vitro and In Vivo After Transplantation in Rats

Abstract: Although ϳ1 million islets exist in the adult human pancreas, current pancreas preservation and islet isolation techniques recover <50%. Presently, cadaveric donors remain the sole source of pancreatic tissue for transplantation. Brain death is characterized by activation of proinflammatory cytokines and organ injury during preservation and reperfusion. In this study, we assessed the effects of brain death on islet isolation yields and functionality. Brain death was induced in male 250-to 350-g Lewis rats by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 36 publications
(42 reference statements)
0
110
2
2
Order By: Relevance
“…Detrimental factors such as brain teriorate posttransplant function (10). As a consequence, reduction of hyperthermia not only prevented a signifideath, surgical trauma, or enzymatic pancreas digestion are characterized by the activation of proinflammatory cant upregulation of proapoptotic proteins such as Bax, Fas, or DNA fragmentation factor, but minimized overand proapoptotic mechanisms affecting islet yield and viability (1, 13,24,28). After intraportal transplantation expression of HSP27, HSP70, or HSP90 as well (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…Detrimental factors such as brain teriorate posttransplant function (10). As a consequence, reduction of hyperthermia not only prevented a signifideath, surgical trauma, or enzymatic pancreas digestion are characterized by the activation of proinflammatory cant upregulation of proapoptotic proteins such as Bax, Fas, or DNA fragmentation factor, but minimized overand proapoptotic mechanisms affecting islet yield and viability (1, 13,24,28). After intraportal transplantation expression of HSP27, HSP70, or HSP90 as well (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, sustained insulin-independence after islet transplantation has been difficult to achieve [1], partly because of a significant loss of islets during brain death, islet isolation, transplantation and revascularisation in the liver [2,3]. Islet apoptosis may be induced by various stress factors such as hypoxia [4] and inflammation [5].…”
mentioning
confidence: 99%
“…Brain death causes up-regulation of pro-inflammatory cytokines in a time-dependent manner (75), hence islets are subject to different stresses during the pancreas procurement which can induce apoptosis. In the previous decades, several studies have shown that improvements in pancreas procurement, islet isolation and culture techniques result in increasing islet yield and subsequently favorable clinical outcomes.…”
Section: Improvement Of Pancreas Procurement Islet Isolation and Culmentioning
confidence: 99%